1996
DOI: 10.1002/(sici)1097-461x(1996)57:4<587::aid-qua7>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of spectroscopic properties of bicyclobutane, tricyclopentane, tricyclohexane, and octabisvalene

Abstract: -The outer-valence ionization potentials, low-lying electronically excited states, and ' J ( c C ) nuclear spin-spin coupling constants of bicyclobutane, tricyclopentane, tricyclohexane, and octabisvalene have been investigated at the ab initio level by using the outer-valence Green function (OVGF), random-phase approximation (RFA), and equations-of-motions (EOM) approaches, which incorporate the main dynamical correlation effects. A comprehensive theoretical prediction of these spectroscopic observables is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(8 reference statements)
2
6
0
Order By: Relevance
“…34 Moreover, with ab initio equa- tions-of-motion calculations, we have previously shown that this situation also holds in the case of the intercage bond of the still elusive bitetrahedrane, 35 and for the bridging bond in bicyclobutane, tricyclopentane, and related systems. 18,36 On this basis, the present theoretical predictions can be regarded with confidence.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…34 Moreover, with ab initio equa- tions-of-motion calculations, we have previously shown that this situation also holds in the case of the intercage bond of the still elusive bitetrahedrane, 35 and for the bridging bond in bicyclobutane, tricyclopentane, and related systems. 18,36 On this basis, the present theoretical predictions can be regarded with confidence.…”
Section: Resultssupporting
confidence: 67%
“…However, by using the present basis set and DFT perturbational approach, previous investigations have reported a satisfactory reproduction of 1 J (CC) for a variety of organic compounds. , On the other hand, the dominant importance of the FC contribution to “normal” coupling constants 1 J (CC) is well documented in the literature . Moreover, with ab initio equations-of-motion calculations, we have previously shown that this situation also holds in the case of the intercage bond of the still elusive bitetrahedrane, and for the bridging bond in bicyclobutane, tricyclopentane, and related systems. , On this basis, the present theoretical predictions can be regarded with confidence.…”
Section: Resultssupporting
confidence: 57%
“…Galasso has applied his EOM method (see section VI.F) to compute spin-spin coupling constants in a large number of polyatomic moleculesssee ref 268. Most of the recent results are for the 1 J(CC) constants across unusual bonds in hydrocarbons, like the bridgehead bond in propellanes 269 or the ultrashort bond in bitetrahedrane.…”
Section: Larger Moleculesmentioning
confidence: 99%
“…When reactant BCB is substituted with 13 C at the 2-position, the BD product may result with the 13 C at either middle or end positions. It is possible to devise a scheme where the intermediate from Figure 8 can be invoked to produce an intermediate diradical yielding CB, which subsequently converts to BD with 13 C substituted according to Schemes 1 and 2. But early studies of the isotope effect of hydrocarbons showed that substitution of 13 C for 12 C was small 54 and would have little effect on changing product ratios or accounting for the mechanism of 13 C substitution.…”
Section: Photochemical Products and Conical Intersectionsmentioning
confidence: 99%